Psychologically Grounded Chatbots in Online Furniture Retail - Pedron, Claudia; Federspiel, Esther (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
High-involvement online purchase decisions are characterized by extensive information processing, perceived risk, and uncertainty. These challenges are particularly visible in furniture retail, where financial investment, long usage cycles, limited physical experience, and symbolic relevance make the purchase decision particularly complex. Although conversational AI is increasingly used in digital commerce, many chatbots remain transaction-oriented and insufficiently address psychological decision dynamics. Using a design-oriented conceptual research approach informed by design science principles, this article develops a phase-sensitive conceptual reference model for psychologically grounded conversational AI in high-involvement online purchasing. Furniture retail serves as an illustrative application context. Chatbots are conceptualized as dialogical decision companions whose roles evolve across the purchasing process, from preference exploration and risk reduction to trade-off moderation and decision stabilization. The model integrates psychological factors such as perceived risk, trust, aesthetic preferences, and sustainability values, as well as chatbot-related design factors such as personalization, usefulness, and interaction quality.